The Relationship between Knowledge, Information Sources and Lifestyle and Myopia Prevention in Students - Simamora, Janner Pelanjani; Hutabarat, Naomi Isabella (Universitas Prima Indonesia, 2024)
Myopia is a refractive error that occurs when distant objects do not focus properly on the retina. The prevalence of myopia cases has increased over time. This study aims to determine the relationship between knowledge, information sources, lifestyle, and the prevention of myopia in class VIII students at SMP Negeri 2 Lintongnihuta with a sample size of 58 students. The sampling technique is that the entire population is sampled. The type of research used is analytical descriptive research with a cross-sectional design. The results showed that the majority of respondents had sufficient knowledge (46.6%), were male (63.8%), 13 years old (83.3%), obtained information from electronic media (58.6%), style adequate living (46.6%), and myopia prevention not good (70.7%). Based chi-square statistical test, there is a relationship between knowledge (p-value < α, namely 0.025 < 0.05), sources of information (p-value < α, namely 0.002 < 0.05) and lifestyle (p-value < α, namely 0.000 < 0.05) with the prevention of myopia in class VIII students. It is hoped that there will be a need to increase knowledge about preventing myopia among students at SMP Negeri 2 Lintongnihuta, Lintongnihuta District, Humbang Hasundutan Regency.